E-Cigarettes and myocardial Infarction: a systemic review and meta-analysis. (11th May 2021) - Sharma, A; Gupta, I; U, V; Golamari, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: With widespread awareness about the harmful effects of traditional smoking, many people are considering the use of an e-cigarette. However, there are many studies which have shown e-cigarettes is not entirely harmless and it's use has been implication in causing major adverse cardiovascular events. Methodology This systemic review strictly adhered to the PRISMA checklist. An electronic search was conducted comprehensively through five databases to find the relevant articles. The odds ratio (OR) was used for comparing groups. Meta-analysis was conducted using R statistical software version 3.4.3. A random-effect model was used. Results: A total of 4 studies were included in the analysis incorporating data on 585, 306 subjects. In these, 19, 435 were e-cigarettes users, while 1693 used only traditional cigarette users, and 553, 095 were non-e-cigarette users. A total of 7.0% of e-cigarette users suffered an MI in their lifetime, while only 6.5% of non-e-cigarette users have had MI. The OR of getting an MI in e-cigarettes users was 1.30 (95% CI = 1.23-1.38, p-value < 0.01) in comparison to non e-cigarette users. While it is 0.61 (95% CI = 0.40 – 0.93, p-value 0.02) when compared with traditional smoking. Conclusion: Those using e-cigarettes have a higher odds of suffering from an MI in comparison to not using e-cigarettes. However, using e-cigarettes reduces the risk of MI by half in comparison to traditional smoking.